What is binocular disparity? - Lappin, Joseph S. (Frontiers in Psychology, 2014)
What are the geometric primitives of binocular disparity? The Venetian blind effect and other converging lines of evidence indicate that stereo-scopic depth perception derives from disparities of higher-order structure in images of surfaces. Image structure entails spatial variations of in-tensity, texture, and motion, jointly structured by observed surfaces. The spatial structure of bin-ocular disparity corresponds to the spatial struc-ture of surfaces. Independent spatial coordinates are not necessary for stereoscopic vision. Stere-opsis is highly sensitive to structural disparities associated with local surface shape. Disparate positions on retinal anatomy are neither neces-sary nor sufficient for stereopsis.